2008
DOI: 10.1002/hep.22221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hepatocyte growth factor–mediated and epidermal growth factor–mediated signaling in transdifferentiation of rat hepatocytes to biliary epithelium

Abstract: Taken together, these data indicate that hepatocyte to BE transdifferentiation is regulated by HGF and EGF receptors and that PI3 kinase-mediated signaling independent of AKT is a crucial component of the transdifferentiation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 43 publications
5
90
0
Order By: Relevance
“…Previous studies also showed that HGF was another promoter of the phenotypic changes of mature hepatocytes. 18,21,22 However, as shown in Figure 1a, our preliminary studies failed to demonstrate significant changes in CK19 and AFP expression after HGF treatment in PLC-5.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous studies also showed that HGF was another promoter of the phenotypic changes of mature hepatocytes. 18,21,22 However, as shown in Figure 1a, our preliminary studies failed to demonstrate significant changes in CK19 and AFP expression after HGF treatment in PLC-5.…”
Section: Discussionmentioning
confidence: 66%
“…[18][19][20][21][22] In these studies, EGF has been shown to be an essential promoter of the phenotypic transdifferentiation of mature hepatocytes. 18,[20][21][22] This study demonstrated that EGF could induce phenotypic changes in HCC similar to those seen in non-cancerous mature hepatocytes. Previous studies also showed that HGF was another promoter of the phenotypic changes of mature hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Recently, we found that tumor necrosis factor-α (TNF-α) significantly enhanced ductular transdifferentiation (Nishikawa et al, submitted for publication).…”
Section: Introductionmentioning
confidence: 99%